Multiligamentous Injury of the Knee: MRI Diagnosis and Injury Patterns - Hansford, Barry Glenn; Yablon, Corrie M. (Seminars in Musculoskeletal Radiology, 2017)
Anterior cruciate and posterior cruciate injuries rarely occur in isolation and are often associated with injuries to the secondary or supporting structures that provide stability against rotational forces. These structures include the posterolateral and posteromedial corner ligaments and tendons, as well as the anterolateral ligament. If injuries to these secondary structures are not appreciated at the time of cruciate ligament reconstruction, an isolated cruciate ligament reconstruction may be predisposed to early failure. Thus it is crucial for radiologists interpreting knee magnetic resonance imaging to understand and report on injury to these ligaments and tendons at the time of initial injury to help the orthopaedic surgeon plan a comprehensive approach to ligament reconstruction. This strategy will ultimately result in improved patient outcomes.
Keywords: knee MRI; posterolateral corner; posteromedial corner; anterolateral ligament; multiligamentous knee injury